Taxonomy and geographic distribution of the species of Centris of the hyptidis group (Hymenoptera: Apidae: Centridini), with description of a new species from central Brazil - Vivallo, Felipe; Melo, Gabriel A. R. (Zootaxa, 2009)
The species of Centris of the hyptidis group are revised. The group, composed by C. hyptidis Ducke, C. hyptidoides Roig-Alsina, and C. thelyopsis n. sp., exhibits unique morphological characters within the genus, like foreand midtrochanters with a laminar expansion at the base, and elaiospathes strongly modified. An updated catalog, and floral and distributional records are provided for each species, as well as an identification key and a distribution map. The male of C. hyptidoides is described for the first time and a modern diagnosis for C. hyptidis is presented. A new species, C. thelyopsis n. sp., is described from Goiás State, in central Brazil. It can be easily distinguished from the two previously known species by its predominant orange pilosity, including that of the hind legs and metasoma.